Trace elements in Ultisol irrigated with landfill leachate and public-supply water - Daniela da C. L. Coelho; Rafael O. Batista; Francisco O. Mesquita; Ketson B. da Silva; Sandra M. C. Alves; Marcelo T. Gurgel (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Landfill leachates have considerable amounts of organic matter and mineral nutrients and, when applied in environmentally adequate amounts, show fertilizing potential for the soil-plant system. This study aimed to analyze the effect of landfill leachate (LFL) and the public-supply water (PSW) depths on the contents of trace elements in an Ultisol. This work was carried out from April 21 to August 21, 2012, in split-split-plot scheme; LFL and PSW depths (T1 - 0 mm of LFL and 1067 mm of PSW; T2 – 60 mm of LFL and 1067 mm of PSW, T3 - 120 mm of LFL and 1067 of PSW, T4 - 180 mm of LFL and 1067 of PSW, and T5 - 240 mm of LFL and 1067 mm of PSW) in the plots, the analyzed layers (0-0.2 m and 0.2-0.4 m) in the subplots and the sampling times (0, 30, 60, 90 and 120 days) in the sub-subplots. Soil samples were collected every 30 days for 120 days to characterize the trace elements Fe, Mn, Pb, Cd, Zn, Cu and Ni. There was leaching of Pb, Cd and Ni in the Ultisol, while the T2 treatment was the most recommended to prevent contamination of groundwater.